Sistem Pemantauan Keberadaan Jamaah Haji Menggunakan GPS Tracking Pada Smartphone Android (Studi Kasus : Kbih Al Ishlahiyyah Al Ghozaliyyah Tuban) - Sisephaputra, Bonda; Supriyanto, Antok; Sutanto, Teguh (Jurnal JSIKA, 2012)
Loss of hajj pilgrims, particularly Indonesia, as a common story in the holy land of Mecca and Medina. Usually it occurs in the early days of arrival. While there are officers of the government that could help solve the problem of pilgrims who get lost, but the numbers are still very limited. Controlling the presence of pilgrims made directly by the supervisor KBIH assisted by the group leader and team leader, but control is still difficult because of the unavailability of good facilities. So to be able to monitor the need for systems that can locate the presence of fossilized pilgrims.A device that allows to build systems that can help counselors to monitor the presence of pilgrims and help the pilgrims to know his position is by using a device equipped with GPS feature, because these devices can be easily carried. Android smartphone are very suitable for the development of this system, because almost all embedded Android smartphone has GPS features. To solve these problem, so we developed an existence of Pilgrims Monitoring System Using GPS Tracking to Android Smartphone that can monitor the presence of pilgrims to facilitate KBIH supervisor from controlling the existence of the pilgrims and help the pilgrims avoid getting lost.   Keywords : GPS Tracking, Hajj Pilgrims, Android, Mobile Application.